Pathogenicity of South African Hymenochaetales taxa isolated from esca-infected grapevines - Mia CLOETE; Lizel MOSTERT; Michael FISCHER; Francois HALLEEN (Phytopathologia Mediterranea, 2015)
Little is known about the pathogenicity and etiology of Hymenochaetales taxa associated with esca in South Africa. Ten South African Hymenochaetales taxa associated with esca in grapevine were subjected to basic enzyme assays to determine which ligninolytic enzymes were secreted by each taxon. In addition, a field trial was undertaken to determine the pathogenicity of these taxa. Twenty-seven fungal isolates and two negative controls were inoculated into wounds made on mature grapevines of the cultivars Shiraz and Mourvédre. Inoculated vines were evaluated for white rot symptoms after 24 months. The results of the enzyme assays indicated a difference in enzyme secretion among taxa and also between isolates of the same taxa. All isolates secreted cellulase and laccase, but there was a difference in isolates’ ability to secrete manganese peroxidase and lignin peroxidase. The results of the pathogenicity trial showed that all of the isolates used were capable of causing the characteristic white rot symptom in the wood. There were clear differences in susceptibility to white rot between the two cultivars tested, namely Shiraz and Mourvédre. The cultivars also differed in which taxa proved to be more virulent. On Shiraz a specific isolate of Taxon 6 (an Inonotus sp.), Phellinus sp. and Inonotus setuloso-croceus were significantly virulent. On Mourvédre, Taxon 3 (an Inocutis sp.) was significantly virulent.